Fabrication of Zirconium Silicate Reinforced Superhydrophobic Coating for the Evaluation of Corrosion-Resistance - Mubarak Ali Muhamath Basha; Sathiya Srinivasan (Acta Chimica Slovenica, 2022)
The present work investigates on anodisation of aluminium in 1.0 M sodium oxalate and methodically evaluates the influence of zirconium silicate as an additive. The effect of additive upon structure, morphology, micro hardness and composition of the coating formed under various anodising conditions has been examined comprehensively. The surface of the coating was modified by stearic acid and its immersion time was optimized. The dependence of surface morphology, kinetic parameters, and microstructural characteristics of the coating on electrolyte /additive concentration, anodising time, and the temperature has also been inspected. X-ray diffraction (XRD), Scanning Electron Microscopy (SEM) combined with EDAX studies indicates the beneficial role of zirconium silicate towards the formation of crystalline coating with improved corrosion-resistant characteristics. The static water contact angle on the surface-modified coatings was 122° ± 0.4°. This contact angle of super hydrophobic coating has been improved by KOH treatment (152.76o ± 0.4°) which is obtained under optimized conditions exhibit the corrosion resistance (1.68 × 108 Ω cm-1)which is nearly 8 times higher than that of bare aluminium (8.36 × 101 Ω cm-1). The efficacies of the surface-modified coatings against bacteria that are commonly encountered in marine (Desulfovibrio desulfuricans) and medical applications (Staphylococcus aureus and Escherichia coli) are also demonstrated.